2017
DOI: 10.1200/jco.2017.35.15_suppl.11066
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic genomic alterations in desmoplastic small round blue cell tumor.

Abstract: 11066 Background: Desmoplastic Small Round Blue Cell Tumor (DSRCT) originates from a cell with multilineage potential. A molecular hallmark of DSCRT is the EWS-WT1 reciprocal translocation. Ewing’s and DSRCT are treated similarly due to similar oncogene activation pathways and DSRCT has been represented in very limited numbers in sarcoma studies. Methods: Thirty-five DSRCT tumors were tested with a multiplatform profiling service (Caris Life Sciences, Phoenix, AZ). Specific tests performed included sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Molecular profiling on 35 DSRCTs sampled from patients having surgery for DSRCT (Caris Life Sciences, Phoenix, AZ) that were compared with Ewing sarcoma revealed low immunogenicity (<10 mutations/Mb) and low frequency of actionable mutations including PD-L1 in both tumor types. High AR expression could present as a potential therapeutic target for DSRCT while taxanes may be more effective in Ewing sarcoma compared to DSRCT based on TUBB3 expression [ 43 ]. Given the male predominance of this subset of disease, it is not surprising that, when compared to Ewing sarcoma, no significant difference was seen in protein expressions with the exception of a significantly higher overexpression of AR in DSRCT (59% versus 3%, p =1.7E-10) and TUBB3 (56% versus 29%, p =0.03) [ 43 ].…”
Section: Molecular Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular profiling on 35 DSRCTs sampled from patients having surgery for DSRCT (Caris Life Sciences, Phoenix, AZ) that were compared with Ewing sarcoma revealed low immunogenicity (<10 mutations/Mb) and low frequency of actionable mutations including PD-L1 in both tumor types. High AR expression could present as a potential therapeutic target for DSRCT while taxanes may be more effective in Ewing sarcoma compared to DSRCT based on TUBB3 expression [ 43 ]. Given the male predominance of this subset of disease, it is not surprising that, when compared to Ewing sarcoma, no significant difference was seen in protein expressions with the exception of a significantly higher overexpression of AR in DSRCT (59% versus 3%, p =1.7E-10) and TUBB3 (56% versus 29%, p =0.03) [ 43 ].…”
Section: Molecular Findingsmentioning
confidence: 99%
“…A phase II study (SARC028) is evaluating the role of pembrolizumab across various sarcoma histologies ( NCT02301039 ) [ 47 ]. None of the patients in a recently reported DSRCT cohort had identifiable tumoral PD-L1 expression by SP142 antibody testing, and the significance of PD-1-positive TILs is unclear at this time [ 43 ]. The composite of tumoral PD-L1 positivity and PD-1 positivity among tumor-infiltrating lymphocytes has been suggested as an indicator of prognosis in soft tissue sarcoma patients [ 45 ].…”
Section: Role Of Immunotherapymentioning
confidence: 99%
“…Not surprisingly, genome sequencing is undergoing widespread implementation into routine cancer patient care ( Supplementary Table 1 ). Molecular profiling is now incorporated into standard practice guidelines recommended by the NCCN while offering research value through facilitating the investigation of potential biomarkers of interest in breast [ 102 – 110 ], colorectal [ 111 – 115 ], gastroesophageal [ 116 – 122 ], hepatobiliary [ 123 – 127 ], pancreatic [ 128 – 130 ], gynecologic [ 131 – 143 ], prostate [ 144 – 152 ], other genitourinary (kidney, germ cell, and bladder) [ 153 – 166 ], lung [ 167 – 179 ], head and neck [ 180 – 187 ], melanoma [ 188 – 194 ], soft tissue sarcomas [ 195 – 204 ], and central nervous system cancers [ 205 – 212 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, one important molecular aberration that distinguishes DSRCT from ES is the increased Androgen Receptor (AR) expression. In a comprehensive analysis of 35 patients [20] with diagnosis of DSRCT using next-generation sequencing, immunohistochemistry and gene amplification tests it was found that the most common alterations that distinguished DSRCTs from ES included higher expression of AR, TUBB3, EGFR, and TOPO2A expression. Independent analysis using RNAseq confirmed higher AR expression from an independent data set of EWS-WT1 fusion-positive DSRCTs compared with ES and a pan-cancer analysis [20].…”
Section: Demographics Of Dsrctmentioning
confidence: 99%